DIETARY HABITS AND RELATED SOCIO-DEMOGRAPHICS AMONG SECONDARY SCHOOL ADOLESCENTS OF ZANZIBAR, TANZANIA (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Background: Adolescence is a period where general health is at its best and stage where risks health behaviour such as unhealthy diets are expressed and increased.Aim: To explore the dietary habits and eating behaviours as well as examined the socio-demographic correlates of healthy eating and snacking habit among adolescents of Zanzibar, Tanzania.Material and Methods: Cross-sectional study among secondary school adolescents. Cluster sampling technique was used and data collected using structured questionnaire. The questionnaire inquired on; socio-demographics, dietary habits and eating behaviours. Frequency distributions, cross-tabulations and Kendall’s correlations were used for analysis.Results: Four hundred adolescents participated in the study, mean age 16.5 years (1.03) and were mostly from socio-demographically advantaged families. Close to a third (28.0%) ate healthy foods and 9.5% ate vegetables on daily basis. Snacking was found in 57.3% of all adolescents and that 33.5% ate either sweets, sugared beverages daily. Younger aged adolescents and those with educated parents were eating healthy compared to their counterparts.Conclusion: Eating healthy foods items was uncommon among the adolescents while snacking was much prevalent habit. Parental education level and employment status was associated with healthy eating and snacking habit; and that healthy eating positive correlated with snacking habits.